Educational Innovation in the 21st Century: Revolutionizing the Classroom - Macias Galeas, Isabel Patricia (2024)
This study addresses educational innovation in the 21st century, highlighting its potential to transform teaching and learning practices in response to the challenges of a globalized and technologically advanced world. With a particular focus on emerging trends and the opportunities presented by educational innovation, this analysis seeks to improve the quality and accessibility of education. Utilizing a methodology of bibliographic review and qualitative analysis, various pedagogical and technological innovations implemented in different educational contexts were examined, especially in the context of the COVID-19 pandemic, which has accelerated the adoption of many of these innovations. The results underscore how these innovations have overcome barriers such as the digital divide and geographical limitations. The conclusions emphasize the need to adapt educational practices to contemporary demands through the integration of emerging technologies and active methodologies. This approach not only facilitates access to knowledge but also promotes more personalized and meaningful learning. This study is useful for educators, administrators, and policymakers interested in implementing innovations that effectively respond to the current needs of education.